2016
DOI: 10.1186/s13104-016-1933-6
|View full text |Cite
|
Sign up to set email alerts
|

Skin diseases among elderly patients attending skin clinic at the Regional Dermatology Training Centre, Northern Tanzania: a cross-sectional study

Abstract: BackgroundAs global population of the elderly continues to rise, a critical need to provide it with health services, including dermatology, will be significant, especially in developing countries like Tanzania. To adequately meet their dermatologic needs, knowledge of local patterns of skin conditions is vital. This study was aimed to describe the spectrum of skin diseases among elderly patients attending skin clinic at the Regional Dermatology Training Centre (RDTC) in Northern Tanzania.MethodsA descriptive h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 22 publications
7
15
1
Order By: Relevance
“…Eczemas were the second-most-commonly observed disorders (34.7%). This contrasts with earlier data from previous studies, which showed that eczema was the most frequent skin illness in most hospitalbased investigations, with rates ranging from 11.9-58.7% (5). The prevalence of eczematous diseases in the elderly in the community-based study reported a higher prevalence similar to our study by 28.7%…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Eczemas were the second-most-commonly observed disorders (34.7%). This contrasts with earlier data from previous studies, which showed that eczema was the most frequent skin illness in most hospitalbased investigations, with rates ranging from 11.9-58.7% (5). The prevalence of eczematous diseases in the elderly in the community-based study reported a higher prevalence similar to our study by 28.7%…”
Section: Discussioncontrasting
confidence: 99%
“…These ndings were similar to those of two other studies, which found that the most common dermatological disorders in older individuals were skin infections (38.61%) and (23.7%), respectively (13,14). However, the study conducted at a tertiary hospital in Northern Tanzania, reported that skin infections and infestations were less prevalent (11%) in elderly patients (5). This disparity in ndings could be explained by the fact that the high frequencies are likely due to the warm and highly humid climate, overcrowding, and poor personal and skin hygiene in the city (15) .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Psoriasis affect patients' perceptions of themselves and this can potentially initiate or exacerbate psychological disorders such as depression, thus proper counselling, empathy and retaining patients in care is absolute. A recent study analyzing skin diseases among elderly patients attending a dermatology unit in Tanzania revealed an overall prevalence of psoriasis to be 7.7%, which is relatively higher than the worldwide prevalence of 2.2-3.9% [10]. This could serve as a wakeup call to raise awareness of the complexity of this multifaceted disease especially as most of the milder cases could go undiagnosed or discovered incidentally.…”
Section: Resultsmentioning
confidence: 99%
“…In ours study, erythroderma constituted the greatest magnitude of skin diseases both during 2019 and 2020 followed by pemphigus vulgaris, eczema and cellulitis. A similar cross-sectional study carried out in Tanzania revealed that eczema was the most frequent dermatological problem followed by papulosquamous disorders, fungal infections and tumors [13]. Likewise, a research among general public attending the Dermatology OPD of a tertiary healthcare facility of Lahore disclosed that most of the patients were 20-40 years old and eczema constituted the greatest magnitude (31.07%) of dermatological illnesses.…”
Section: Introductionmentioning
confidence: 80%